FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM JASA PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zahara Fatimah; Frangky Silitonga (JURNAL MATA PARIWISATA, 2022)
The study of testing the impact of several factors on stock price of hotel industry listed in Indonesia stock exchange is based on an approach to the constant growth of dividend discount model. By using regression analysis, this study provides evidence that stock price is influenced by book value equity per share and return on equity. The other factors of the research model such as return on asset (ROA), debt to equity ratio, stock return, market risk and return on the market index have no impact to the stock price. In general, it’s discovered that all of the factors have weak influence in explaining stock price variation which means that mostly it is determined by other various things